The role of peer support in recovery among clients with mental illness attending the psychiatric service in a tertiary hospital in Malaysia: a qualitative study - Izzul Hazwan, Sulaiman; Nur Iwana, Abdul Taib; Jane Tze Yn, Lim; Tuti Iryani, Mohd Daud; Marhani, Midin (BioMed Central Ltd., 2024)
Background The understanding that mental health recovery is a personal and subjective experience informs mental health policies in many countries. However, most of the populations in these studies are from the West, limiting their applicability in Asia. Peer support in mental health refers to helping and mentoring people who have overcome similar obstacles. Despite being proven to be effective in promoting recovery, little is known about its use in Malaysian psychiatric patients. This study aims to explore the participants’ perspectives on their concept of recovery and how the peer support group (PSG) aid them to achieve recovery.